A Rare Case of Deep Pelvic Endometriosis Presenting with Serous Ascites and Infertility - Türkan Gürsu; Güldeniz Desteli; Hulusi Bülent Zeyneloğlu (Gynecology Obstetrics & Reproductive Medicine)
In this study it is aimed to define a rare case of deep pelvic endometriosis with massive serous ascites and infertility.